The Lanao Sultanate in the 17th Century Zakāt System with Special Reference to the Islamic Perspective of Al-Māwardī - SOHAYLE M. HADJI ABDUL RACMAN; DR. HASSAN SHAKEEL SHAH; DR. MOHAMMAD AYAZ; DR. KALIM ULLAH (International Journal of Islamic Economics and Governance, 2020)
Literature studies show that there is a sizable research gap vis-à-vis the Sunni Islamic perspectives on zakāt system of the Lanao Sultanate. To fill in this research gap, this paper is intended to explore in-depth the Sunni Islamic perspectives of the practices of the Maranaos in Lanao on zakāt system with special reference to the Islamic perspective of al-Māwardī on zakāt system. This works has used secondary data sources such as books, theses and journals. This study will be of significant use as a reference material for the researchers. This research promotes open and constructive debates on how applied Islamic governance helped to develop the civil and religious life of the natives in the Philippines in the 17th century. The recommendations of this work provide important inputs for the state policy makers to promote better Islamic governance in the Muslim majority regions of Philippines. This study contributes to the body of knowledge and academia on regional studies on Islamic civilization in Southeast Asia as well as on the significant impact of the Lanao Sultanate to the ways of life of the Maranao communities This study also recommends that the policy makers should devise policies that promote Islamic zakāt system in the Muslim dominated areas of Philippines. Such policies could be highly effective in eradicating poverty and also in promoting the distribution of wealth for the quality life of masses in general.